A comprehensive review on medicinal plant extract-based nanoparticles for dye degradation - Giriraj Tailor; Jyoti Chaudhary; Saurabh Singh; Deepshikha Verma; Deepak Kumar (Chemistry of Inorganic Materials, 2025)
Green synthesis is a sustainable, dependable, and environmentally safe method of producing a range of materials and nanomaterials, including metal and metal oxide nanoparticles, which is why materials scientists are so interested in it. Research on plant-derived nanoparticles has increased significantly in recent years because of its many benefits, which include stable products, inexpensive synthesis costs, and environmentally benign methods. When discharged into the environment, toxic effluents like dyes contaminate water sources, threaten aquatic life, and cause deadly diseases in humans. The use of nanoparticles, particularly biosynthesized ones, in eliminating dyes from industrial effluent is the main focus of this review. This paper examines a variety of biosynthesized nanoparticles that are employed to break down different contaminants in wastewater. The review discusses the formation mechanisms, characterizations, and influencing variables of metal and metal oxide nanoparticles, green synthesis methodologies along with their dye degradation activities and photocatalytic mechanism.